Depression in Patients with Tinnitus: A Literature Review - Anggraini, Yulia (Scientia Psychiatrica, 2023)
Tinnitus has been a worldwide complaint and refers to the bothersome auditory perception in the absence of external acoustic or electric stimulus. There is no consolidated criterion for tinnitus definition for the purpose of research. The most common definition of tinnitus demonstrates that tinnitus must exceed a 5-min duration. Tinnitus affecting 8 to 25.3% of the population of the United States and the world. Psychiatric disorders such as anxiety and depression are often comorbid in patients with chronic tinnitus, and these conditions can not only be troublesome and debilitating, they have been shown to increase morbidity and the risk of suicide among patients with tinnitus. This literature review aims to identify association between depression and tinnitus. The articles selected were all published within the past five years from PubMed. 7 articles were obtained and were included in the review. Based on the articles, hearing loss, noise, stress and depression have proven to be markers without differentiating between cause and effect. The etiology and pathogenesis of the interrelationships between psychological complaints or illnesses and tinnitus stress are not sufficiently understood despite intensive research efforts. In conclusion, the question of whether depression is the cause of the tinnitus or tinnitus is the cause of the depression, or whether there are other dependencies, remains unanswered.